2014
DOI: 10.1039/c4bm00193a
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to balance covalent and non-covalent biomolecule attachment within collagen-GAG biomaterials

Abstract: Strategies to integrate instructive biomolecular signals into a biomaterial are becoming increasingly complex and bioinspired. While a large majority of reports still use repeated treatments with soluble factors, this approach can be prohibitively costly and difficult to translate in vivo for applications where spatial control over signal presentation is necessary. Recent efforts have explored the use of covalent immobilization of biomolecules to the biomaterial, via both bulk (ubiquitous) as well as spatially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…In such cases, 1-ethyl-3-(3 dimethylaminopropyl)-carbodiimide (EDC) chemistry is often used to covalently link polymeric and biological molecules together. 28 Although previous groups have demonstrated some success in binding biologically relevant peptides or proteins to synthetic polymers, 2931 the process is limited by chemical cross-linking reagents and suboptimal reaction environments. In addition, conjugation chemistry results in poor yields, and does not provide strict control over surface distribution of the biological molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, 1-ethyl-3-(3 dimethylaminopropyl)-carbodiimide (EDC) chemistry is often used to covalently link polymeric and biological molecules together. 28 Although previous groups have demonstrated some success in binding biologically relevant peptides or proteins to synthetic polymers, 2931 the process is limited by chemical cross-linking reagents and suboptimal reaction environments. In addition, conjugation chemistry results in poor yields, and does not provide strict control over surface distribution of the biological molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds were further crosslinked (room temperature, 1.5 h) in a solution of 1‐ethyl‐3‐[3‐dimethylaminopropyl] carbodiimide hydrochloride (EDC) (Sigma–Aldrich) and N ‐hydroxysulfosuccinimide (NHS) (Sigma–Aldrich) at a molar ratio of 5:2:1 EDC:NHS:COOH. For immobilized estradiol experiments, BSA‐E2 (0–1,000 nM E2; Sigma–Aldrich) was immobilized into the scaffolds during crosslinking at a molar ratio of 5:12.5:1 EDC:NHS:COOH using a previously described stepwise reaction (Pence et al, ; Shen et al, ). Equivalent dosages of soluble E2 versus covalently‐bound BSA‐E2 were determined as equivalent molar ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Scaffolds support significant cell invasion and metabolite biotransport (O'Brien et al, 2007). Recently, methods have been described to incorporate exogenous biomolecular signals in soluble (Caliari and Harley, 2014), covalently-bound (Alsop et al, 2014), or transiently sequestered (Hortensius and Harley, 2013;Pence et al, 2014) forms to instruct cell behaviors. Here, we examined the impact of exogenous E2 on separate and combined cultures of endometrial epithelial cells from an adenocarcinoma (Ishikawa 3-H-12 cells) and endothelial cells (human umbilical vein endothelial cells, HUVECs) commonly used in many investigations of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[100] When evaluated in the laboratory, the efficiency of EDC crosslinking of Concanavalin A (ConA) to collagen glycosaminoglycan (CG) scaffolds was significantly increased in the presence of greater concentrations of ConA, a 5:12.5:1 EDC-NHS-COOH ratio, and with the step crosslinking approach versus bulk crosslinking. [8] Pence and Harley demonstrated that the source of collagen can significantly change the immobilization of proteins during crosslinking. [8] Murphy and O’Brien evaluated a range of pore sizes in collagen glycosaminoglycan scaffolds of identical composition, crosslinking, and synthesis methods.…”
Section: Challenges In Development Of Biomimetic Scaffoldsmentioning
confidence: 99%
“…[8] Pence and Harley demonstrated that the source of collagen can significantly change the immobilization of proteins during crosslinking. [8] Murphy and O’Brien evaluated a range of pore sizes in collagen glycosaminoglycan scaffolds of identical composition, crosslinking, and synthesis methods. [13,101] They demonstrated that wide differences in adhesion, migration, and differentiation in a range of 85–325 μm in pore sizes, with the larger pore size demonstrating the best results.…”
Section: Challenges In Development Of Biomimetic Scaffoldsmentioning
confidence: 99%